Frontispiece: 3‐O‐Sulfation of Heparan Sulfate Enhances Tau Interaction and Cellular Uptake. Issue 5 (24th January 2020) - Zhao, Jing; Zhu, Yanan; Song, Xuehong; Xiao, Yuanyuan; Su, Guowei; Liu, Xinyue; Wang, Zhangjie; Xu, Yongmei; Liu, Jian; Eliezer, David; Ramlall, Trudy F.; Lippens, Guy; et al.
Abstract : Proteins L. Wang, C. Wang, and co‐workers report in their Research Article on page 1818 how a rare 3‐ O ‐sulfation of heparan sulfate significantly enhances tau binding and cellular uptake of tau, thus providing a novel target for treating Alzheimer′s disease.